Perineural Versus Intravenous Dexamethasone as an Adjuvant for Peripheral Nerve Blocks: A Systematic Review and Meta-Analysis - Chong, Matthew Alan; Berbenetz, Nicolas Matthew; Lin, Cheng; Singh, Sudha (Regional anesthesia and pain medicine, 2017)
BACKGROUND AND OBJECTIVESDexamethasone is a useful adjuvant in regional anesthesia that is used to prolong the duration of analgesia for peripheral nerve blocks. Recent randomized controlled trials (RCTs) have demonstrated conflicting results as to whether perineural versus intravenous (IV) administration is superior in this regard, and the perineural use of dexamethasone remains off-label. Therefore, we sought to perform a systematic review and meta-analysis of RCTs. METHODSIn accordance with PRISMA guidelines, we performed a random-effects meta-analysis of RCTs comparing perineural versus IV dexamethasone with duration of analgesia as the primary outcome. RESULTSEleven RCTs met the inclusion criteria with a total of 1076 subjects. Perineural dexamethasone prolonged the duration of analgesia by 3.77 hours (95% confidence interval [CI], 1.87–5.68 hours; P < 0.001) compared to IV dexamethasone, with high statistical heterogeneity. For secondary outcomes, perineural dexamethasone prolonged the duration of both motor (3.47 hours [95% CI, 1.49–5.45]; P < 0.001) and sensory (2.28 hours [95% CI, 0.38–4.17]; P = 0.019) block compared to IV administration. Furthermore, perineural dexamethasone patients consumed slightly less oral opioids at 24 hours than IV dexamethasone patients (7.1 mg of oral morphine equivalents [95% CI, 0.74–13.5 mg]; P = 0.029), and there were no statistically significant differences in the other secondary outcomes. Notably, no increase in adverse events was detected. CONCLUSIONSPerineural dexamethasone prolongs the duration of analgesia across the RCTs included in our meta-analysis. The magnitude of effect of 3.77 hours raises the question as to whether perineural dexamethasone should be administered routinely over its IV counterpart—or reserved for selected patients where such prolongation would be clinically important.